Reading inclusion divergently : articulations from around the world - Amrhein, Bettina, 1972-; Naraian, Srikala; Forlin, Chris (Emerald Publishing Limited, 2022)
This volume offers a critical orientation to inclusive education by centering the learnings that emerge from regional struggles in the world to actualize global ideals and commitments. Grounded in assumptions that challenge medicalized notions of disability and difference, the inquiries within this book register a range of theoretical frameworks. Such frames compel us to both interrogate the foundational premises within global discourses of inclusion and to inquire into the complexities wrought by entrenched systems of schooling. Collectively, they articulate the inseparability of inclusive education from historical processes that include conditions in post-colonial/post-war contexts as well as "developed" regions. The book therefore acknowledges and values the fluidity of inclusive processes that cannot be neatly pre-defined. This conscious awareness of the contingent nature of inclusive practice suggests new modes of coming to know inclusion for the authors in this book. Their chapters explore methodological practices that can re-direct inquiries to hold such complexity while retaining commitments to inclusion.
Keywords: Inclusive education.; Mainstreaming in education.; Education -- Inclusive Education.; Inclusive education, mainstreaming.; elektronické knihy; electronic books